Mitochondrial Function and Reactive Oxygen/Nitrogen Species in Skeletal Muscle - Chen, Ming-Ming; Li, Yan; Deng, Shou-Long; Zhao, Yue; Lian, Zheng-Xing; Yu, Kun (Frontiers in Cell and Developmental Biology, 2022)
Skeletal muscle fibers contain a large number of mitochondria, which produce ATP through oxidative phosphorylation (OXPHOS) and provide energy for muscle contraction. In this process, mitochondria also produce several types of “reactive species” as side product, such as reactive oxygen species (ROS) and reactive nitrogen species (RNS), which have attracted interest. Mitochondria have been proven to have an essential role in the production of skeletal muscle reactive oxygen/nitrogen species (RONS). Traditionally, the elevation in RONS production is related to oxidative stress, leading to impaired skeletal muscle contractility and muscle atrophy. However, recent studies have shown that the optimal RONS level under the action of antioxidants is a critical physiological signal in skeletal muscle. Here, we will review the origin and physiological functions of RONS, mitochondrial structure and function, mitochondrial dynamics, and the coupling between RONS and mitochondrial oxidative stress. The crosstalk mechanism between mitochondrial function and RONS in skeletal muscle and its regulation of muscle stem cell fate and myogenesis will also be discussed. In all, this review aims to describe a comprehensive and systematic network for the interaction between skeletal muscle mitochondrial function and RONS.